Wildfires and water chemistry: effect of metals associated with wood ash. Issue 8 (26th July 2016) - Cerrato, José M.; Blake, Johanna M.; Hirani, Chris; Clark, Alexander L.; Ali, Abdul-Mehdi S.; Artyushkova, Kateryna; Peterson, Eric; Bixby, Rebecca J.
Abstract : The dissolution of metal-bearing carbonate and oxide phases in ash, and metal re-adsorption to ash can impact water quality after post-fire storm events. Abstract : The reactivity of metals associated with ash from wood collected from the Valles Caldera National Preserve, Jemez Mountains, New Mexico, was assessed through a series of laboratory experiments. Microscopy, spectroscopy, diffraction, and aqueous chemistry measurements were integrated to determine the chemical composition of wood ash and its effect on water chemistry. Climate change has caused dramatic impacts and stresses that have resulted in large-scale increases in wildfire activity in semi-arid areas of the world. Metals and other constituents associated with wildfire ash can be transported by storm event runoff and negatively affect the water quality in streams and rivers. Differences among ash from six tree species based on total concentrations of metals such as Ca, Al, Mg, Fe, and Mn were identified using non-metric multidimensional analysis. Metal-bearing carbonate and oxide phases were quantified by X-ray diffraction analyses and X-ray spectroscopy analyses. These metal-bearing carbonate phases were readily dissolved in the first 30 minutes of reaction with 18 MΩ water and 10 mM HCO3 − in laboratory batch experiments which resulted in the release of metals and carbonates in the ash, causing water alkalinity to increase. However, metal concentrations decreased over the course of the experiment, suggesting that metals re-adsorb to ash. Our results suggest that the dissolution of metal-bearing carbonate and oxide phases in ash and metal re-adsorption to ash are relevant processes affecting water chemistry after wildfire events. These results have important implications to better understand the impact of wildfire events on water quality.